2009
DOI: 10.1042/cs20090055
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fatigue syndrome: illness severity, sedentary lifestyle, blood volume and evidence of diminished cardiac function

Abstract: The study examined whether deficits in cardiac output and blood volume in a CFS (chronic fatigue syndrome) cohort were present and linked to illness severity and sedentary lifestyle. Follow-up analyses assessed whether differences in cardiac output levels between CFS and control groups were corrected by controlling for cardiac contractility and TBV (total blood volume). The 146 participants were subdivided into two CFS groups based on symptom severity data, severe (n=30) and non-severe (n=26), and two healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 50 publications
7
55
1
Order By: Relevance
“…All control subjects were screened as sedentary based on their response to a questionnaire upon recruitment. This was subsequently confirmed by the aerobic capacities obtained (VO2 max) (Hurwitz et al, 2010). Adjusted maximum VO2 levels were comparable between GWI and control groups but were significantly lower for the CFS disease control group (p < 0.05).…”
Section: Subject Assessmentsupporting
confidence: 62%
“…All control subjects were screened as sedentary based on their response to a questionnaire upon recruitment. This was subsequently confirmed by the aerobic capacities obtained (VO2 max) (Hurwitz et al, 2010). Adjusted maximum VO2 levels were comparable between GWI and control groups but were significantly lower for the CFS disease control group (p < 0.05).…”
Section: Subject Assessmentsupporting
confidence: 62%
“…11 Following our reports, Hurwitz et al reported that severe CFS patients have lower cardiac volume assessed by echocardiography and lower total blood volume, plasma volume, and red blood cell volume measured by dual tag blood volume assessments than controls, suggesting a comorbid hypovolemic condition. 18 Interestingly, in 2003 Peckerman et al reported that, using impedance cardiography in the supine and standing positions, cardiac output is significantly lower in a severe CFS group than in controls and less-ill patients. 19 Many CFS patients have low cardiac output, and the resulting low circulatory flow state may make it difficult for patients to meet the demands of daily activity, and it may also lead to fatigue and other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The interesting paper in the present issue of Clinical Science by Hurwitz et al [1] entitled ‘Chronic fatigue syndrome: illness severity, sedentary lifestyle, blood volume and evidence of diminished cardiac function’ is important because it aligns current thinking regarding CFS (chronic fatigue syndrome) with ongoing work concerning circulatory regulation, particularly as it relates to decreased overall blood volume and issues of orthostatic intolerance. In addition, despite significant cardiac findings, the paper [1] effectively puts to rest arguments in favour of a causative role for heart disease in CFS.…”
mentioning
confidence: 99%